Primer on development and aid effectiveness (IBON International Quezon CityPH, 2007)
Aims to explain the aid effectiveness agenda in the overall context of development issues and concerns such as debt, debt cancellation, and increasing ODA for poverty reduction, and achieving the Millennium Development Goals. Addresses the perspectives and concerns of grassroots and membership based civil society organisations (CSOs).
Keywords: AID PROGRAMMES